1978
DOI: 10.1111/j.1365-2222.1978.tb01504.x
|View full text |Cite
|
Sign up to set email alerts
|

Humidifier fever and endotoxin exposure

Abstract: Summary Three cases of humidifier fever were detected in an office environment. Flavobacteria were found in the contaminated water in a humidifier. After an experimental exposure, the three persons with previous symptoms suffered from fever and slight respiratory symptoms. A leucocytosis and an increase in the number of segmented white blood cells were found the day following the exposure. General immuno‐globulins as well as antibodies to Flavobacterium and endotoxin were slightly elevated in the exposed group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(50 citation statements)
references
References 14 publications
2
47
0
1
Order By: Relevance
“…In previous studies similar symptoms have been described in relation with endotoxin fever, humidifier fever, or Monday morning fever and extrinsic allergic alveolitis (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). As etiologic agent(s) fungi, bacteria, amoeba, endotoxins, and antigenic material from humidifiers have been suggested.…”
mentioning
confidence: 82%
“…In previous studies similar symptoms have been described in relation with endotoxin fever, humidifier fever, or Monday morning fever and extrinsic allergic alveolitis (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). As etiologic agent(s) fungi, bacteria, amoeba, endotoxins, and antigenic material from humidifiers have been suggested.…”
mentioning
confidence: 82%
“…The fact that the onset of symptomsin the present case occurred immediately following the use of the humidifier for the first time favors this notion. It has been suggested that bacterial endotoxin may play a role in humidifier lung (12)(13)(14)(15). The reports of bath water fever and humidifier lung demonstrated high concentrations of endotoxin (0.…”
Section: Discussionmentioning
confidence: 99%
“…Inhaled endotoxin events associated with water Rylander et al (1978) were among the first to theorize that endotoxin was the causal agent in unexplained cases of fever after exposure to contaminated water in humidifiers and in a sauna (Kohler et al 1976;Metzger et al 1976;Pickering et al 1976). This was accomplished by measuring endotoxin O antigen antibody titers in three subjects who developed 'humidifier disease' from a humidifier contaminated with two unidentified species of Flavobacterium.…”
Section: Introductionmentioning
confidence: 99%